C Community Service Activities Socialization And Education Dagusibu As An Effort To Improve Adolescents' Knowledge Of Use Gastric Pain Medication (Gastroistestinal) In Teenagers In Sma Plus Cadet Akterlis Medan - Tambunan, Rika Puspita (INSTITUT KESEHATAN DELI HUSADA, 2025)
This Community Service Activity aims to increase adolescents' knowledge about the use of gastrointestinal pain medication through socialization and education about DAGUSIBU (Get, Use, Save, Dispose of) at SMA Plus Taruna Akterlis Medan. This activity was held on May 9, 2025 and was attended by 30 students. The methods used include providing materials, question and answer sessions, and educational games. The results of the activity showed that students had high enthusiasm and were able to understand the material presented. It is hoped that the knowledge gained can help students in using drugs correctly and maintaining their health.